Chapter Osservazioni tassiane a margine dell'opera di Boccaccio - Incandela, Marika (Studi e saggi, 2022)
The essay proposes a study of the relationship between Tasso and Boccaccio, analysing the references to the ancient auctoritas present in Tasso's theoretical production. The sixteenth-century poet's interest in Boccaccio's works can be found in the author's epistolary, in the letters in which Tasso claims to be in possession of some of his texts or in those in which he explicitly requests them. As with Dante and Petrarch, the reading is careful and inclined to take the ancient source as a model for observations of a rhetorical, linguistic-grammatical and metrical nature. These observations form a non-systematic corpus of reflections on poetic language, an authentic reflection of an intimate dialogue between the author and Boccaccio.